Design and Development of a Web-based Self-Service Ordering and Product Review System at Jalur Langit Coffee - kurniawan, Muhammad David; Arifin, Muhammad; Fithri, Diana Laily (Sistemasi: Jurnal Sistem Informasi, 2025)
Digital transformation in the culinary industry, particularly in coffee shops like Jalur Langit Coffee, demands innovative solutions to address service inefficiencies and long queues that often hinder customer satisfaction. This study aims to design an interactive and responsive web-based information system that facilitates ordering, payment, and product reviews through a self-service model using QR code technology. The system was developed using the Waterfall methodology, encompassing requirements analysis, system design using Unified Modeling Language (UML), implementation, testing, and ongoing maintenance. It also incorporates a Customer Relationship Management (CRM) approach by applying the Customer Satisfaction Score (CSAT) metric to evaluate customer ratings of products. The results indicate a 95% success rate in ordering and payment processes, with the kopi tubruk product receiving a 78% satisfaction level based on CSAT scores. This research is limited to a single café location and does not yet support integration with external payment platforms. The system enhances service efficiency, product review management, and overall product quality, while also strengthening customer loyalty through review data analysis.